(untitled) (Multidisciplinary Journal of Science and Technology, 2023)
The role and importance of folk music in the development of the art of singing; The role of the teachings of Eastern thinkers in the development of the art of singing; It was discussed about the organization of the features of the tradition of teacher and discipleship in the art of national singing; it is important to study the ideological and artistic features of Uzbek folk singing.